A framework to explain the in-match decision-making of elite Australian football coaches. (July 2023) - Aarons, Mitchell F.; Vickery, Will; Bruce, Lyndell; Young, Chris M.; Dwyer, Dan B.
Abstract: The ability to make effective decisions is an important function of any football coach, whether during training, team selection, match-day performance or post-match player evaluation. It is not yet known how elite Australian football coaches make decisions during matches, in time-constrained but well-resourced environments. This study is the first to explore the decision-making of elite Australian football coaches during matches, in pursuit of identifying opportunities to improve the translation and implementation of research findings into the competitive match environment. Using semi-structured interviews and thematic analysis, a six-stage framework of the decision-making of elite Australian football coaches during matches was developed. The stages include (1) Opportunity trigger, (2) Understand the opportunity, (3) Determine the need for action, (4) Explore options, (5) Take action and (6) Evaluate the decision. Coaches relied on subjective and objective sources of information and consulted with assistant coaches, performance analysts, and sport scientists. The findings enable researchers to ensure future interventions to improve decision-making during matches are well integrated. They also provide an opportunity for coaches to reflect on their own decision-making process, identifying targeted areas for improvement in their own practice. Highlights: Insights into how elite football coaches make decisions during matches are explored in the context of Australian football. A framework is proposed to explain and understand the coach's in-match decision-making, guided by bounded rationality. Opportunities for targeted reflection on coaching practice and research intervention are presented.